2010
DOI: 10.1002/jbmr.315
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and physical activity in relation to the incidence of hip fracture in postmenopausal women

Abstract: Hip fracture risk is known to increase with physical inactivity and decrease with obesity, but there is little information on their combined effects. We report on the separate and combined effects of body mass index (BMI) and physical activity on hospital admissions for hip fracture among postmenopausal women in a large prospective UK study. Baseline information on body size, physical activity, and other relevant factors was collected in 1996-2001, and participants were followed for incident hip fractures by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 39 publications
7
76
2
1
Order By: Relevance
“…Our findings are in accordance with other studies which reported that fractures in obese women contribute significantly to the total burden of fractures in the older population (7,21,22). In a United Kingdom Cohort study, which followed 925,345 women for 6.2 yrdthe Million Women Studyd40% of women with hip fractures were overweight or obese (22). Furthermore, a reanalysis of the National Health and Nutrition Examination Survey I in 2012 showed that 46% of hip fractures occurred in obese or overweight women (21).…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…Our findings are in accordance with other studies which reported that fractures in obese women contribute significantly to the total burden of fractures in the older population (7,21,22). In a United Kingdom Cohort study, which followed 925,345 women for 6.2 yrdthe Million Women Studyd40% of women with hip fractures were overweight or obese (22). Furthermore, a reanalysis of the National Health and Nutrition Examination Survey I in 2012 showed that 46% of hip fractures occurred in obese or overweight women (21).…”
Section: Discussionsupporting
confidence: 96%
“…To the best of our knowledge, this is the first study to evaluate the association between obesity and fractures in Latin America. Our findings are in accordance with other studies which reported that fractures in obese women contribute significantly to the total burden of fractures in the older population (7,21,22). In a United Kingdom Cohort study, which followed 925,345 women for 6.2 yrdthe Million Women Studyd40% of women with hip fractures were overweight or obese (22).…”
Section: Discussionsupporting
confidence: 95%
“…(30) In the Million Women Study in the UK, almost one-half of all postmenopausal hip fractures occurred in women who were overweight or obese: 40% were overweight (BMI 25-29.9 kg/m 2 ) and 9% were obese (BMI 30 kg/m 2 ). (17) In a large longitudinal study of older U.S. men, 68% of all incident clinical fractures and 62% of incident hip fractures occurred in those who were overweight or obese; 19% of all clinical fractures and 13% of hip fractures occurred in obese men. (31) For this Perspective we performed an analysis of the National Health and Nutrition Examination Survey I (NHANES) (see Supporting Information Appendix for analytical methods) and again found that the majority of men over 65 years old who experience hip fracture were overweight or obese (Fig.…”
Section: Predominance Of Overweight and Obesity Among Fracture Casesmentioning
confidence: 99%
“…1). Armstrong and colleagues (17) also found that in women the protective effect of increasing BMI on hip fracture risk was most notable at low BMI ranges, and that increasing BMI above the normal range had much less impact on risk, emphasizing that the BMI-fracture risk relationship is nonlinear. Even more recently, an analysis in the Global Longitudinal Study of Osteoporosis in Women (GLOW), involving >60,000 postmenopausal women in 10 countries, confirmed the increased risk of fracture in underweight women but showed no protective effect of obesity in women.…”
Section: Introductionmentioning
confidence: 99%
“…The primary reason was inferred to be that of the various dimensions that are encompassed by frailty criteria, the primary physiological dimension includes various evaluations such as physical activity, muscular, balance, self-perceived activity, and gait speed levels, which are correlated with fracture risk. Armstrong et al (2011) indicated that physical activity was related to hip bone fracture incidence rate. Muir et al (2013) suggested that the dynamic parameters of balance were related to falls and bone fracture history among older adults.…”
Section: Discussionmentioning
confidence: 99%